2017
DOI: 10.3390/en10081170
|View full text |Cite
|
Sign up to set email alerts
|

Insulation Strength and Decomposition Characteristics of a C6F12O and N2 Gas Mixture

Abstract: This paper explores the decomposition characteristics of a new type of environmentally friendly insulating gas C 6 F 12 O and N 2 mixed gas under AC voltage. The breakdown behavior of 3% C 6 F 12 O and N 2 mixed gas in quasi-uniform field was investigated through a breakdown experiment. The self-recovery of the mixed gas was analyzed by 100 breakdown experiments. The decomposition products of C 6 F 12 O and N 2 under breakdown voltage were determined by gas chromatography-mass spectrometer (GC-MS). Finally, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In order to explore the discharge decomposition path of c-C 4 F 8 and the effect of O 2 on its decomposition, a thermodynamic and kinetic combination method was used to analyze the orientation and mechanism of the reaction based on density functional theory (DFT). With regard to theoretical knowledge of calculations, it has been described in detail in our previous work [30,31]. The Dmol3 package was used to process exchange-related interactions using a local density approximation (LDA-PWC) approach to optimize the structure of c-C 4 F 8 and O 2 [25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to explore the discharge decomposition path of c-C 4 F 8 and the effect of O 2 on its decomposition, a thermodynamic and kinetic combination method was used to analyze the orientation and mechanism of the reaction based on density functional theory (DFT). With regard to theoretical knowledge of calculations, it has been described in detail in our previous work [30,31]. The Dmol3 package was used to process exchange-related interactions using a local density approximation (LDA-PWC) approach to optimize the structure of c-C 4 F 8 and O 2 [25].…”
Section: Discussionmentioning
confidence: 99%
“…The solvent delay time was 0.1 min; the detector voltage threshold was 100 and the voltage was 0.1 kV. The specific steps can be found in [26][27][28][29][30]. Figure 3 shows the surface of the ball electrode before and after breakdown of pure c-C4F8, c-C4F8/N2 gas without O2 and with 3% O2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The decomposition products of the mixed gas after breakdown are analyzed to obtain fluorocarbons such as CF 4 , C 2 F 6 , C 3 F 6 . 12,13 Referring to Table I, considering the GWP, cost and toxicity, C 6 F 12 O is a good choice. Previous studies have found that C 6 F 12 O with N 2 mixed breakdowns are more likely to produce solid products, CO 2 is more suitable as a buffer gas.…”
Section: Introductionmentioning
confidence: 99%